Neutrophil-to-lymphocyte ratio predicts functionally significant coronary artery stenosis in patients with stable coronary artery disease - Samet Yılmaz; Uğur Canpolat; Kazim Başer; Sefa Ünal; Mevlüt Serdar Kuyumcu; Sinan Aydoğdu (KARE Publishing, 2018)
Objective: The aim of this study was to determine the relationship between the neutrophil-to-lymphocyte ratio (NLR) and the functional severity of coronary stenosis assessed according to the fractional flow reserve (FFR) in stable coronary artery disease (CAD). Methods: The clinical and laboratory data of 420 patients who underwent index coronary angiography for stable angina pectoris were analyzed retrospectively. The functional severity of an intermediate lesion was determined by FFR. An FFR value of >0.80 was considered non-significant (Group 1), whereas ≤0.80 was accepted as significant stenosis (Group 2). Results: A total of 137 (32.6%) patients had functionally significant coronary artery stenosis. The median NLR value was significantly greater in Group 2 compared with Group 1 [3.13 (0.93-9.75) vs 2.22 (0.75-6.02); p<0.001]. In multivariable logistic regression analysis, the Gensini score [odds ratio (OR): 1.04; 95% confidence interval (CI): 1.02-1.06; p<0.001], diabetes mellitus (OR: 2.56; 95% CI: 1.38-4.75; p=0.003), smoking (OR: 2.09; 95% CI: 1.12-3.94; p=0.021), and NLR (OR: 1.62; 95% CI: 1.26-2.09; p<0.001) were found to be independent predictors of the presence of functionally significant coronary stenosis using an FFR value of ≤0.80. The optimal cut-off value of NLR for predicting functionally significant coronary stenosis was 2.3. An NLR value greater than 2.3 had a sensitivity of 72% and a specificity of 61% to predict stenosis with an FFR value of ≤0.80. Conclusion: The pre-angiographic NLR is a simple, noninvasive, and inexpensive biomarker that was significantly higher in patients with functionally significant coronary stenosis; it can be used to predict the hemodynamic severity of intermediate coronary stenosis in patients with stable CAD.